2018
DOI: 10.18203/2349-2902.isj20182239
|View full text |Cite
|
Sign up to set email alerts
|

The role of C-reactive protein as a predictor of difficult laparoscopic cholecystectomy or its conversion

Abstract: Background: Laparoscopic cholecystectomy (LC) can be the easiest or the most difficult laparoscopic operation. Conversion to open surgery has been a traditional marker of difficult LC. Recent studies have shown that C-reactive protein (CRP) may be helpful to surgeon in knowing the pathological condition of gall bladder before removal. Aim of this study was to evaluate the role of CRP as a predictor of difficult LC or its conversion.Methods: This study was done from 1 march 2016 to may 2017 in department of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Emergency patients had significantly higher Nassar grades compared to patients undergoing elective surgery. While no studies comparing Nassar grade levels based on the type of surgical indication for cholecystectomy were found, previous research indicated a potential connection between complications during laparoscopic cholecystectomy and variations in C-reactive protein (CRP) levels, with notable discrepancies in CRP values and conversion criteria across different studies1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . While our study did not specifically investigate the relationship between CRP levels and conversion, this aspect warrants attention in future research to understand better how CRP may be linked to the Nassar scale.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency patients had significantly higher Nassar grades compared to patients undergoing elective surgery. While no studies comparing Nassar grade levels based on the type of surgical indication for cholecystectomy were found, previous research indicated a potential connection between complications during laparoscopic cholecystectomy and variations in C-reactive protein (CRP) levels, with notable discrepancies in CRP values and conversion criteria across different studies1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . While our study did not specifically investigate the relationship between CRP levels and conversion, this aspect warrants attention in future research to understand better how CRP may be linked to the Nassar scale.…”
Section: Discussionmentioning
confidence: 99%
“…This further supports the benefit of performing a delayed laparoscopic cholecystectomy after a "cooling off" period. 22,23 The readmission risk before DLC is significant (13.5% over 2 months; 22.5% over the median waiting time [5 months, 9 days]) and must be minimized. Recurrent admissions ultimately result in increased morbidity that may actually outweigh the benefit of DLC.…”
Section: Discussionmentioning
confidence: 99%
“…1 Laparoscopic cholecystectomy (LC) is the gold standard procedure for cholecystectomy in patients with gall stones. 2 Difficult laparoscopic cholecystectomy (DLC) is faced in about 2-7% cases of laparoscopic cholecystectomy procedures. 3 Different definitions exist, but the conversion rate and iatrogenic injuries are considered frequently as indicators of a difficult procedure.…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous studies have identified predictors for Difficult laparoscopic cholecystectomy, these predictors are as follows: male sex, advanced age, acute and chronic cholecystitis, obesity, liver cirrhosis and surgical experience whereas laboratory parameters as leucocyte count and c-reactive protein. 2 There are some existing scales that evaluate the risk of conversion from laparoscopic to open surgery, [6][7][8] but few scales that predict Difficult laparoscopic cholecystectomy. 9 C-reactive protein (CRP) is one identified as predictor of such complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation